2019
DOI: 10.5829/ije.2019.32.08b.01
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ultrasound Assisted Extraction: Determination of Quercetin for Antibacterial and Antioxidant Activities of Iranian Propolis

Abstract: A B S T R A C TPropolis was used as medicine, cosmetic and beverage additives since past decades. The most important active compounds in the propolis are phenolic and flavonoids, which are in the resin category. The purpose of this study was to measure the total amount of flavonoids and quercetin in propolis of northern Iran and compare obtain data with different extraction methods. The soxhlet, maceration and microwaveultrasound-assisted extraction (MUAE) were conducted for comparison of the extraction effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The antioxidant activity (47.18%) was higher than water extracts of propolis obtained by Mahdavi‐Roshan et al ( 2022 ) (15.83%) and lower than the ethanolic propolis extract reported by Ibrahim and Alqurashi ( 2022 ) (94.45%). Previous studies have reported that Iranian propolis extracts as a natural source of various antioxidants (Mahdavi‐Roshan et al, 2022 ; Mohammadzadeh et al, 2007 ; Najafpour Darzi et al, 2019 ). The origin of propolis, the extraction method, and the type of solvent used for extraction influence propolis extract characterization (Mafra et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant activity (47.18%) was higher than water extracts of propolis obtained by Mahdavi‐Roshan et al ( 2022 ) (15.83%) and lower than the ethanolic propolis extract reported by Ibrahim and Alqurashi ( 2022 ) (94.45%). Previous studies have reported that Iranian propolis extracts as a natural source of various antioxidants (Mahdavi‐Roshan et al, 2022 ; Mohammadzadeh et al, 2007 ; Najafpour Darzi et al, 2019 ). The origin of propolis, the extraction method, and the type of solvent used for extraction influence propolis extract characterization (Mafra et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…(3) BI = 100(X − 0.31) ∕ 0.17 et al, 2007;Najafpour Darzi et al, 2019). The origin of propolis, the extraction method, and the type of solvent used for extraction influence propolis extract characterization (Mafra et al, 2022).…”
Section: Characterization Of Ethanolic Propolis Extractmentioning
confidence: 99%
“…Apart from flavonoids, many phenolic compounds are contained in honeycomb and propolis extracts (Asem et al, 2020;Mokosuli & Rombot, 2023;Bouchelaghem et al, 2022;Mokosuli et al, 2019;Jamil and Zhari et al 2019;Mouhoubi et al, 2016). Quercetin is a group of flavonoids most abundant in propolis obtained using ethanol (Wang, 2016;Najafpour et al, 2019). However, the geographical location of the hive, the season, and the bee-feed plants significantly affect the secondary metabolite content of propolis (Mokosuli et al, 2023;Kurek et al, 2022;Alvear et al, 2021;Sarikahya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The pre‐optimised procedures from Najafpour Darzi et al . (2019) and Setyaningsih et al . (2019) were used with required modification.…”
Section: Methodsmentioning
confidence: 97%